(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Tourism with its functions has become one of the key sectors of economic development in any region. It creates jobs, improves the living standards of the population and ensures the rapid development of the region. Tourism is a sector that provides growth in financial resources in a short period of time with little investment. Within the framework of this article, an attempt was made to analyze tourism development opportunities on the example of the village of Kalavan (Chambarak district, Gegharkunik Region).